Algorithmic node classification in AND/OR mobile workflow graph. (3rd February 2020) - Ali, Ihtisham; Bagchi, Susmit
The data-intensive applications employ complex workflow graph models in dynamic networks having heterogeneity and mobility of nodes, which result in enhanced end-to-end delay in executions. The current workflow models lack structural stability for visualising a complex workflow graph. This paper proposes a hybrid AND/OR mobile workflow graph (MWG) model to visualise a fully conditioned complex workflow graph containing mobile nodes. This paper proposes nodes validity detection (NVD) algorithm for classifying the total number of nodes in the AND/OR MWG. Furthermore, nodes criticality detection (NCD) algorithm is also proposed to identify the set of critical nodes in the AND/OR MWG aiming to enable efficient analysing, mapping and scheduling of complex workflow graphs in a dynamic network environment. The algorithms are implemented and evaluated on Java platform and, the regression analysis is performed to project the algorithmic performances. A detailed comparative analysis with other works is presented in this paper.